2022
DOI: 10.3389/fpsyt.2022.838700
|View full text |Cite
|
Sign up to set email alerts
|

Trait Impulsivity and Choice Impulsivity in Young Adult Students With Probable Binge Eating Disorder

Abstract: BackgroundBinge eating disorder (BED) as a public health problem has been included in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). Akin to addictive disorders, impulsivity-related neuropsychological constructs might be potentially involved in the onset and development of BED. However, it remains unclear which facets of impulsivity are connected to overeating and binge eating behaviors among non-clinical populations. The present study aimed to detect the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…This questionnaire consisted of demographic information (ie, age, gender, years of education, ethnicity, home locality, smoking and drinking behaviors) and a Chinese version of the Binge Eating Scale (BES), 44,45 which has been properly used among Chinese college students in previous studies. 46,47 A total of 862 students voluntarily responded to the screening questionnaire, 63 of whom were identified as individuals with pBED, with a total score ≥ 18 on the BES. 45,48 All 63 students voluntarily participated in our study and were subsequently scheduled to complete a person-to-person interview in the laboratory.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…This questionnaire consisted of demographic information (ie, age, gender, years of education, ethnicity, home locality, smoking and drinking behaviors) and a Chinese version of the Binge Eating Scale (BES), 44,45 which has been properly used among Chinese college students in previous studies. 46,47 A total of 862 students voluntarily responded to the screening questionnaire, 63 of whom were identified as individuals with pBED, with a total score ≥ 18 on the BES. 45,48 All 63 students voluntarily participated in our study and were subsequently scheduled to complete a person-to-person interview in the laboratory.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…A recent study [23] found that higher scores on the BIS-11 subscale "attentional impulsiveness" were observed in normal-weight individuals (at risk for binge eating disorder). "Attentional impulsiveness" has been shown to be associated with binge eating in both normal-weight women [24] and those with obesity [25].…”
Section: Impulsivity and Unhealthy Eatingmentioning
confidence: 99%
“… 25 In comparison to children and adolescents, young adults (eg, college students) actually have easier access to food in China and appear to be at a higher risk of developing binge-eating problems, particularly when they face heavy academic pressure and social competition. 24 , 26 , 27 Unfortunately, the validation and psychometric properties of the SCBES in Chinese young adults remain unclear. Moreover, the cross-cultural adaptability of the BES among young populations in China has limited evidence available.…”
Section: Introductionmentioning
confidence: 99%